Multiscale Structural Patterns of Intertidal Salt Marsh Vegetation in Estuarine Wetlands and Its Interactions with Tidal Creeks - Jianfang Hu; Jiapan Yan; Zhenbang Bian; Zhaoning Gong; Duowen Zhu (Journal of Marine Science and Engineering)
The intertidal zones of estuarine wetlands serve as critical components in maintaining and promoting the sustainable development of regional ecosystems. Salt marsh vegetation, a crucial element of these zones, is experiencing significant deterioration across multiple scales due to various stressors. Despite considerable attention given to the spatial patterns and temporal evolution of salt marsh vegetation, few studies have quantitatively assessed its dynamic interactions with tidal creeks. Tidal creeks serve as primary conduits for material, energy, and information exchange between intertidal zones and adjacent ecosystems. There is a complex feedback mechanism between the development of the tidal creeks and vegetation communities. We investigated the distribution patterns and successional characteristics of salt marsh vegetation at both landscape and pixel scales, with particular emphasis on coupling dynamics with tidal creeks. Our results revealed a distinct spatial gradient in vegetation distribution across the study area. While the invasion of S. alterniflora exhibited limited direct competitive effects on S. salsa, it demonstrated significant influence on tidal creek geomorphological evolution. Notably, S. salsa exhibited pronounced sensitivity to hydrological conditions, with its growth being substantially constrained by tidal creek development and associated soil modifications.